Information technology policy and the digital divide lessons for developing countries - Kagami, Mitsuhiro; Tsuji, Masatsugu; Giovannetti, Emanuele; Edward Elgar Publishing (Cheltenham [England] ; Northampton, Mass. : Edward Elgar Pub., 2004)
The proliferation of new information technologies throughout the world has raised some important questions for policymakers as to how developing countries can benefit from their diffusion. This important volume compares the advantages and disadvantages of the IT revolution through detailed studies of a variety of developed and developing nations and regions: Argentina, Estonia, the EU, India, Japan, Korea, Mexico, South Africa, Thailand and the USA.
pt. 1. Country/area studies -- pt. 2. Challenging issues.
Includes bibliographical references and index.
Keywords: Information technology -- Government policy -- Developing countries; Information technology -- Government policy; Electronic books